Assessment of New Onset Arrhythmias After Transcatheter Aortic Valve Implantation Using an Implantable Cardiac Monitor - Nozica, Nikolas; Siontis, George C. M.; Elchinova, Elena Georgieva; Goulouti, Eleni; Asami, Masahiko; Bartkowiak, Joanna; Baldinger, Samuel; Servatius, Helge; Seiler, Jens; Tanner, Hildegard; Noti, Fabian; Haeberlin, Andreas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Transcatheter aortic valve implantation (TAVI) is associated with new onset brady- and tachyarrhythmias which may impact clinical outcome. Aims To investigate the true incidence of new onset arrhythmias within 12 months after TAVI using an implantable cardiac monitor (ICM). Methods One hundred patients undergoing TAVI received an ICM within three months before or up to five days after TAVI. Patients were followed-up for 12 months after discharge from TAVI for the occurrence of atrial fibrillation (AF), bradycardia (≤30 bpm), advanced atrioventricular (AV) block, sustained ventricular and supraventricular tachycardia. Results A previously undiagnosed arrhythmia was observed in 31 patients (31%) and comprised AF in 19 patients (19%), advanced AV block in 3 patients (3%), and sustained supraventricular and ventricular tachycardia in 10 (10%) and 2 patients (2%), respectively. Three patients had a clinical diagnosis of sick-sinus-syndrome. A permanent pacemaker (PPM) was implanted in six patients (6%). The prevalence of pre-existing AF was 28%, and 47% of the patients had AF at the end of the study period. AF burden was significantly higher in patients with pre-existing (26.7% [IQR 0.3%; 100%]) compared to patients with new-onset AF (0.0% [IQR 0.0%; 0.06%]; p=0.001). Three patients died after TAVI without evidence of an arrhythmic cause according to the available ICM recordings. Conclusions Rhythm monitoring for 12 months after TAVI revealed new arrhythmias, mainly AF, in almost one third of patients. Atrial fibrillation burden was higher in patients with prevalent compared to incident AF. Selected patients may benefit from short-term remote monitoring.